History of the Reserve Bank of India, 1935-51. - Reserve Bank of India; Simha, S. L. N.; Deshmukh, Chintaman Dwarkanath (Bombay, 1970)
This book covers the history of the Reserve Bank of India from inception. It is one of the oldest Central Banks in the developing countries.
Bibliography: p. 863-867.
osc 6/6/17
Loans
Keywords: Central Banking